The Protective Effect of Melatonin on the Retinas of Rats with Streptozotocin-Induced Diabetes Mellitus - Atas, Mustafa; Citirik, Mehmet; Sonmez, Kenan; Celiker, Ulku (Ortadogu Ad Pres & Publ Co, 2011)
Objective: To investigate the protective effect of melatonin on the retinas of rats with streptozotocin (STZ)-induced diabetes mellitus (DM). Material and Methods: Three groups of seven male Wistar rats were enrolled in this study: (1) a diabetic group, (2) a diabetic group treated with melatonin, and (3) control group. Diabetes was induced with a single dose of 60 mg/kg intraperitoneal (i.p). STZ. In addition melatonin (10 mg/kg/day) was injected i.p. to rats in the treatment group. All animals were euthanized 30 days later. Oxidative damage was examined by measuring retinal malondialdehyde (MDA) levels. Results: The mean MDA levels in tissue weight of retinas were 55.68 +/- 6.04 per 100 mg in diabetic rats induced with STZ, 36.13 +/- 7.48 per 100 mg in diabetic rats treated with melatonin, and 23.04 +/- 4.03 per 100 mg tissue in control group. Retinal MDA levels were found different significantly in both diabetic group and melatonin-treated diabetic group compared to the control group (p< 0.001). There was also a difference between the diabetic and melatonin-treated diabetic groups for retinal MDA levels (p< 0.01). MDA levels of diabetic animals treated with melatonin were not different from control group (p> 0.05). Conclusion: Our study revealed that the melatonin improved the retinal damage in diabetic male rats induced with STZ and melatonin had a protective effect against the oxidative damage of DM.
Melatoninin streptozosin ile uyarilmış diabetes mellitus'lu farelerin retinalan üzerindeki koruyucu etkileri
Keywords: Diabetes mellitus; experimental; melatonin; mitochondrial oxidative damage endonuclease; retina